Efeito da calagem e adubação potássica no crescimento e nutrição da cultura da mamona (Ricinus communis L.) - Tiritan, Carlos Sérgio; Calonego, Juliano Carlos; Santos, Diego Hernrique dos [UNESP] (My University, 2010)
The castor bean is an oilseed crop of outstanding importance in Brazil and worldwide. Besides the wide application in chemical industry, is important due to its tolerance to drought, making it a viable crop for the semi-arid region of Brazil, where there are few agricultural alternatives. However, this culture is not unique to semi-arid region and is also planted with excellent results in various regions of the country. The study aimed to evaluate the effects of liming and potassium fertilization on the crop of castor bean. The experiment was conducted in a greenhouse in a randomized complete block randomized in a factorial 3 x 2, where the first factor consisted of potassium (0, 30 and 60 kg ha-1) and in the presence or absence lime to raise the base saturation to 60%. It was found that liming in combination with an intermediate dose of K2O (30 kg ha-1) elevates the production of dry mass of the area, however not change the concentration nutrients in the castor bean.

A mamoneira é uma oleaginosa de destacada importância no Brasil e no mundo. Além da vasta aplicação na indústria química, é importante devido à sua tolerância à seca, tornando-se uma cultura viável para a região semi-árida do Brasil, onde há poucas alternativas agrícolas. No entanto, esta cultura não é exclusiva da região semi-árida, sendo também plantada com excelentes resultados em diversas regiões do país. O trabalho teve por objetivo avaliar os efeitos da calagem e da adubação potássica na cultura da mamona. O experimento foi conduzido em casa de vegetação com delineamento experimental em blocos completos ao acaso, no esquema fatorial 3 x 2, onde o primeiro fator constou de doses de potássio (0, 30 e 60 kg ha-1) e o segundo a presença ou ausência de calagem, para elevar a saturação por bases a 60%.Verificou-se que a calagem em combinação com uma dose intermediária de K2O (30 kg ha-1) eleva a produção de massa seca da parte área, no entanto não altera os teores de nutrientes na planta de mamona.
Effect of liming and potassium fertilization on growth and nutrition of castor oil culture (Ricinus communis L.)